Effects of bypass fat on postpartum reproductive performance in dairy cattle - Nirwan, Surendar Singh; Mehta, Jitendra Singh; Kumar, Ashok; Kumar, Pramod; Kumar, Arvind; Singh, Vikramjit (Indian Journal of Dairy Science, 2019)
This study was conducted to determine the effects of bypass fat on postpartum reproductive performance in dairy cattle. A total of 40 advance pregnant crossbred dairy cows of 2nd to 5th parity were randomly divided into two groups, control (n=10) and treatment (n=30). The control animals were maintained on routine standard feeding schedule. The treatment animals in addition to routine standard feeding schedule, were supplemented orally daily with extra 100 g of bypass fat (Enerfat, Kemin) for about 2 weeks before expected date of calving and continued one week after calving. The level of bypass fat was then increased as per the milk production @ 10 gram per litre of milk produced until 60 days postpartum limiting to maximum of 250 gram/day. Blood samples were collected from each animal at 2 week prior to expected date of calving (-14), day 0, 10, 20 and 30 of calving, for the estimation of various blood biochemical parameters. Gross uterine involution and the interval from calving to first estrus occurrence were recorded. Bypass supplementation non-significantly reduce uterine involution time and time from calving to first postpartum observed estrus. Peripartum bypass fat supplementation significantly (P